The cathedral of lost souls - Brackston, Paula (Brackston, Paula. Hecate Cavendish, 2025)
"Hereford, England 1881. The adventure continues! After the fire and the tumultuous events in the cathedral library, Hecate is determined never again to come so close to losing the beloved mappa mundi. She has shown herself to be the greatest threat to the Essedenes and their plans and they will stop at nothing to be rid of her. With the help of her archeologist father, and the support of the redoubtable and loyal Inspector Winter, she must take the fight to her enemies. But the numbers of Embodied Spirits are growing with terrifying speed, and an atmosphere of violence and danger has taken hold of the ancient city of Hereford. Hecate dare not trust anyone beyond her inner circle, no matter how benevolent they might seem. Nor will she risk the lives of those she loves ever again. The goddess Hekate has called her to action. She must draw upon all her gifts, and the assistance of her family of ghostly allies, if the city is not to be lost to darkness forever"--